World trade law and renewable energy : the case of non-tariff barriers - Howse, Robert (UN New YorkUS, 2009)
Examines whether and to what extent under the law of the WTO government, policies to promote renewable energy may be disciplined as non-tariff barriers. Examines also whether and to what extent WTO law could be used to challenge or discipline policies (regulatory barriers) that disadvantage renewable energy.